Characteristics of Sharia Crowdfunding as an Alternative to Financing the Development of the National Capital City - Dyah Ochtorina Susanti; Aan Efendi; Ahmad Suhaimi (Yuridika, 2024)
This research started from the construction of the new National Capital City of the Nusantara which has not yet been completed and requires a very large budget. In this regard, a financing model is needed that can be used as an alternative financing for the development of the new National Capital City. The aim of this research is to find the characteristics of sharia crowdfunding as an alternative financing in the process of building the new National Capital City. The research method used is a normative juridical research method with a statutory and a conceptual approach. The results of this research show that there are several characteristics of sharia crowdfunding as an alternative financing for the development of the New National Capital, namely: it is only intended for halal projects and products so that it complies with sharia principles and is free from interest rates; there is fairness in the distribution of profit and loss margins using a profit-sharing system; and supervised by the Sharia Supervisory Board.